The Consumption Behavior of Moslem: A Maqashid Shariah Approach toward Foundational Consumptioan Theory in Islam Economics - Muhammad Ulul Azmi (AL-FALAH : Journal of Islamic Economics, 2019)
Purposes: This study discusses explaining about Muslim consumers in using maqoshid based on shariah.Design/Methodology/Approach: this study uses a type of qualitative research based on the literature study.Findings: The results of this study indicate that the benefits obtained from buying goods and services obtained with sincere intentions for worship will produce the goal of mashlahah that can be realized with halal activities. Islam has allowed its people to produce lawful things to produce something useful. In the view of Islam, Muslims must buy goods and services with a principled principle that is approved by Tayyiban in verse Al-Baqarah verse 168 and one of them is to ask our permission (hifdz nafs).Originality/Value: The paper introduce how the muslim consumption behaviour studied through maqashid shariah view. This declared the study succesfully offer new perspective in understanding moslem behaviour in consumption in difference approach, or perspective.